Konstribusi Pola Asuh Permisif terhadap Kemandirian Anak Di Taman Kanak-Kanak Aisyiyah VI Ulak Karang, Padang - Putri, Yanti; Aulia, Prima (Indonesian Journal of Islamic Early Childhood Education, 2019)
The purpose of this study was to determine the contribution of permissive parenting to the independence of children in Aisyiyah VI Ulak Karang Padang Kindergarten. This can be seen from the fact that there are still children who are not independent, this type of research is correlation using quantitative methods. The population in this study were all parents. The samples in this study were saturated samples, which were all parents sampled. Data collection techniques are questionnaires and written data collection lists. Data analysis techniques using product moment formulas were analyzed using the SPSS version 16. Based on data analysis, the contribution coefficient of permissive parenting toward children's independence was 0.076. The correlation coefficient between permissive parenting and children's independence is 0.275. This means that permissive upbringing of 27.5% on the independence of children is significant at the level of 5%. It can be concluded that permissive parenting has a significant contribution to the independence of children in Aisyiyah VI Ulak Karang Padang Kindergarten by 27.5%.